Strategi Pembelajaran E- Learning Biologi pada Masa Pandemi COVID-19 - Nur'aeni, Annisa Latifah; Rochintaniawati, Diana (Publisher by: Papanda Publisher, 2023)
E-learning has been implemented in every school during the COVID-19 pandemic. E-learning is expected to be able to facilitate the learning process without the limitations of space and time and the learning strategies needed so that the material can be delivered in accordance with the learning objectives. The purpose of this study was to determine e-learning learning strategies during the covid-19 pandemic. The method used is descriptive qualitative. The instruments used are questionnaires and interviews. The result of the research is that the e-learning that has been applied gets a different response for each student. A total of 52.5% of students are more comfortable studying face to face. The obstacles faced during e-learning are that teachers cannot assess student attitudes, and students find it difficult to ask questions to learn